Semiotic Aspects of Accounting - Masztalerz, Marek (Studia Oeconomica Posnaniensia, 2013)
The purpose of this paper is to determine the semiotic aspects of accounting. First, it discusses the essence of a strategic-informational paradigm for accounting and the relationships between producers and users of information. Next, it presents the subjects of interest to semiotics as the study of signs and, using the analogy method, identifies and discusses key research issues in the areas of syntax, semantics and pragmatics on the basis of accounting theory.